Exploring the interface between the microfoundations of organizational ambidexterity and corporate entrepreneurship: a systematic review - Schilling, Nils Jakob (2022)
This thesis, “Exploring the Interface between the Micro foundations of Organizational Ambi-dexterity and Corporate Entrepreneurship: A Systematic Review” contributes to the emerging stream of research that addresses the micro foundations of organizational ambidexterity, i.e., what actors, behaviors, contexts, and interactions address the exploration-exploitation paradox. This work attempts to integrate existing research by conducting a systematic literature review(SLR) combined with qualitative content analysis. Through data synthesis and interpretation, the author proposes a model that delineates the interface between corporate entrepreneurship(CE)and individual ambidexterity by specifying the multilevel relationships between these constructs moderated by contextual as well as cognitive factors.